143. VMAT pre-treatment verifications using Gafchromic™ EBT3 and FILM QA software. (December 2018) - Stella, G.; Cavalli, N.; Bonanno, E.; Amico, A.; Gueli, A.M.; Girlando, A.; Marino, C.
Abstract : Purpose: The aim of this work is to optimize the procedures for VMAT patient-specific quality assurance for conventionally fractionated and SBRT treatments using Gafchromic™ EBT3 film dosimetry and FilmQA software. Methods: 16 VMAT treatment plans (8 conventionally fractionated and 8 SBRT) calculated with EclipseTM TPS and delivered with TrueBeam 2.5 have been analyzed. Plans were verified with two different QA methods: routinely pre-treatment verification system, based on EPID images and EPIQA software and dose map measurements by Gafchromic™ EBT3 film dosimetry digitized with Epson 10000 XL and analyzed with FILM QA software. 6 MV, 10 MV and 10 FFF photon beams were used to obtain calibration dose curves from 0 to 25 Gy and to study energy dependence. Triple-channel method was used to improve film dosimetry accuracy. To eliminate scan-to-scan variability and uncertainty therefrom, EBT3 films exposed to each VMAT arc were coupled (and digitalized in a single scan) to two reference films: one film exposed to a known dose and one unexposed film[1] . This allows to obtain a linear dose scaling on the calibration curve and therefore a more accurate dose map. The choice of the reference dose value was made on the basis of its density distribution on the plane delivered for each individual arc (Fig. 1). Pre-treatment verifications were quantified using the global gamma index approach with 3%/3 mm criteria and 95% passing rate. Results: For conventionally fractionated plans the average passing rate was 98.8% and 97.6%, for EBT3&FilmQA and Epid&EPIQA respectively; instead for SBRT plans the average was 97.6% and 96.3% respectively (Table 1). Conclusions: Under the experimental conditions described above, the use of EBT3 film dosimetry analyzed with FilmQA software shows to be an accurate method for VMAT conventionally fractionated and SBRT treatment plans verifications.